The Influence of Incentives and Work Discipline on Employee Performance (Study on Pharmaceutical Companies) - Umban Adi Jaya; Indarta Priyana; Intan Rikhe; Rizki Chrisulianti; Herni Herdiani (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Indonesia’s pharmaceutical industry grows 7-10% yearly with a market over IDR 100 trillion. However, companies like PT Bina San Prima struggle to improve employee performance, unsure which incentives and discipline policies work best to boost productivity and stay competitive. The main objective of this research is to investigate how incentives and adherence to rules impact the performance of employees at PT Bina San Prima, which is a pharmaceutical company located in Sukabumi. To achieve this, a quantitative method was employed, involving the use of multiple linear regression analysis to assess the connection between different factors. The study included all staff members of PT Bina San Prima, with a total of 51 participants chosen through a method of probability sampling. Information was gathered via surveys using a scale of measurement, with tests conducted to confirm the accuracy and consistency of the data-collecting tools. The examination findings reveal that both rewards (X1) and adherence to rules (X2) positively and notably impact employee productivity (Y), with adherence to rules having a more pronounced effect. An 82% coefficient of determination (R²) signals that the combined variables of rewards and adherence to rules can account for the majority of fluctuations in employee productivity, although 18% can be attributed to other factors. This research proposes enhancing discipline schemes and enhancing rewards to enhance employee productivity. Weaknesses of this research include the concentration on a restricted number of variables and the utilisation of a quantitative method that disregards the qualitative aspect.